PENGARUH ROE, CR, SIZE, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - Siddik, Muhammad Hafiz; Chabachib, Mochammad (Diponegoro Journal of Management, 2017)
This research was conducted to examine the effect of Firm’s Value that valued by Price to Book Value (Price to Book Value) from Profitability (Return On Equity), Liquidity (Current Ratio), Size of Firms (Size), and Institutional Ownership (K_INST), and with Capital Structure (DER) as the mediatior variable.We use Property and Real Estate firms that listed on Indonesia Stock Exchange (IDX) through period 2011-2015 and 2012-2016 with signalling theory as a sample of research and based on purposive sampling, we selected 41 firms as the sample of this research. We are using path analysis to examine the effect, and using analytical methods, classical assumptions test that consist of normality test, multicollinearity test, model fit, and residual covariance test.The result shows that simultantly using path analysis, ROE and Size have affected DER, and contrast with Institutional Ownership and CR which doesnt. With value of c.r of -3,882 from ROE proven that ROE have negative effect toward PBV. In the other hand, PBV affected with positive effect from Size with 6,098 points of c.r value. Significant relation occured from DER with 0,018 p value and -2,357, also CR with 0,020 and -2,329 c.r. Non-significant relation occured with ROE, Size, and Institutional Ownership with p value of 0,262, 0,966, and 0,709. Also, DER can mediate the relation between ROE through PBV with p sobel’s value of 0,0439. This research also found that with adjusted r- square, DER have 14,2% described with the variables, followed by PBV that have described by ROE, CR, Size, Institutional Ownership, and DER by 10,8%.